The poetics of literary transfer in early modern France and England - Melehy, Hassan (Ashgate, 2010)
Du Bellay -- Defending the space of early modern culture -- Time in Rome -- Dream language -- Spenser -- Translation, imitation, ruin -- Visions of Spenser -- Antiquities of Britain -- Montaigne -- Institutional authority -- Words of vanity -- America, the end of western dreaming -- Shakespeare -- Sonnets and time -- Old and new Roman times -- Representation of the other